Policy Success in Canada Cases, Lessons, Challenges - Lindquist, Evert; Howlett, Michael; Skogstad, Grace; Tellier, Geneviève; 't Hart, Paul (Oxford University Press, 2022)
This book offers twenty-two in-depth case studies of public policies and programs of both provincial and federal governments in Canada that have been markedly successful. Using a common analytical framework, each case study describes the history and evolution of the policy, and assesses the extent of its programmatic, process, political and long-term success. Combined, the cases provide a unique collection of stories about instances in which Canadian institutions and policymakers actually worked as taxpayers would hope they always do. The volume provides a key and open access resource for teachers and researchers of both Canadian and comparative public policy.